A New Version of Iterative Method for Solving Riemann Problem (Journal of Computational Mathematics, 2018)
A new version of iterative method for solving Riemann problem of gas dynamics is presented. In practice the new procedure exhibited a good convergence in cases where Riemann solution involves a strong rarefaction wave or two rarefaction waves. In the other cases the new version is identical with Godunov procedure.